PENGARUH KEADILAN ORGANISASI, KEPUASAN KERJA, TERHADAP TURNOVER INTENTION KARYAWAN BAGIAN PENJUALAN PADA PT. AGUNG AUOTOMALL KOTA BENGKULU - Erwin Juliadi; Adi Sismanto; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
PT. Agung Automall Kota Bengkulu is a subsidiary of the Agung Concern group which operates as a Toyota main dealer. The formulation of the problem is whether organizational justice and job satisfaction have a significant effect on turnover intention of PT employees. Agung Automall Bengkulu City. This study aims to determine the effect of organizational justice, job satisfaction, on turnover intention of employees of PT. Agung Automall Bengkulu City. This study used a sample of 62 respondents using total sampling technique. Data collection techniques using questionnaires and literature review. Data analysis techniques using multiple linear regression. This research uses validity test, reliability test, classical assumption test, followed by using hypothesis testing using SPSS. Based on the results of multiple linear regression analysis, Organizational Justice (X1) and Job Satisfaction (X2) have a negative effect on Turnover Intention (Y), this is evidenced by the regression equation Y = 19.109 +0. 252 X1 + 0.19 X2 and a determination coefficient of R2 = 0.142 which means Organizational Fairness (X1), and Job Satisfaction (X2) contributes 14.2% influence on Turnover intention (Y) at PT. PT. Agung Automall Bengkulu City and 86.2% are influenced by other variables which are not explained in this study. From the results of hypothesis testing using the t test and f test with the help of SPSS prongram, it can be seen that the variables of Organizational Justice (X1) and Job Satisfaction (X2) have a value of -2,756> .1,670 and -2,306> .1.670 Thus Ho is rejected and Ha is accepted. . This means that together, Organizational Justice and Job Satisfaction affect the Turnover intention of PT. Agung Automall Bengkulu City.